ENGLISH LANGUAGE ABILITIES AND KNOWLEDGE OF ADULT LEARNERS IN A DISTANCE EDUCATION PROGRAMME - Pawanchik, Shahrier; Faiz Hilmi, Mohd; Yahaya, Fatan Hamamah (European Scientific Journal, ESJ, 2014)
The decline in English language proficiency among students who enter public universities is still debatable. Looking at in microcosm, the majority of Malaysian students leave the school system with a poor grasp of English despite having been exposed to the language for eleven or more years. Although both intrinsic and extrinsic motivations have been given, these motivations have been unsuccessful in reaching the greater majority. This research paper will focus on the abilities and knowledge of adult learners who are doing a distance education programme at a university in Malaysia. Findings of this research will provide information for curriculum developers at public universities offering distance education programmes to decide whether they need to revamp their present English courses or design new courses in order to meet the students’ needs and expectations.